DEPRESIUNEA FĂRĂU.CARACTERIZARE GEOMORFOLOGICĂ (PANGEEA, 2025)
Fărău Plateau. Geomorphological characterization. Fărău Plateau is located between two major rivers: Mureş and Târnava Mică. Because of this settlement, the plateau has a serie own characteristics of all environmental components: relief, hydrology, climate, fauna, flora etc. The paper attempts a definition and geomorphological unit placement in major establishments, Târnavelor Plateau and Transylvanian Plateau. It makes a detailed description of the main geomorphological processes affecting the reief of Plateau: fluvial erosion and landslides.